Puppet 5 Beginner's Guide - Third Edition Go from newbie to pro with Puppet 5 - Arundel, John (Packt Publishing Limited, 2017)
bPuppet 5 Beginner's Guide, Third Edition is a practical guide that gets you up and running with the very latest features of Puppet 5./bh2About This Book/h2ulliDevelop skills to run Puppet 5 on single or multiple servers without hiccups/liliUse Puppet to create and manage cloud resources such as Amazon EC2 instances/liliTake full advantage of powerful new features of Puppet including loops, data types, Hiera integration, and container management/li/ulh2Who This Book Is For/h2Puppet 5 Beginner's Guide, Third Edition is designed for those who are new to Puppet, including system administrators and developers who are looking to manage computer server systems for configuration management.